Evaluation of Trichoderma atroviride and Trichoderma longibrachiatum as biocontrol agents in controlling red pepper anthracnose in Korea - Kim, Seung Hwan; Lee, Younmi; Balaraju, Kotnala; Jeon, Yongho (Frontiers in Plant Science, 2023)
Anthracnose disease is a serious threat to red pepper crops in Korea and many other countries, resulting in considerable yield losses. There are now no effective control techniques available except for fungicide sprays, which may directly impact consumers. This study aims to investigate the biological activity of Trichoderma isolates in controlling red pepper anthracnose caused by Colletotrichum acutatum in vitro and in the field. Out of 11 Trichoderma isolates screened for biocontrol agents against three fungal pathogens, including C. acutatum; two effective Trichoderma isolates, T. atroviride ATR697 (ATR697) and T. longibrachiatum LON701 (LON701) were selected for further investigation. Using the overlapping plates experiment, it was discovered that the volatile organic compounds (VOCs) produced by ATR697 strongly inhibited C. acutatum mycelial growth to a larger extent than the isolate LON701. A cellophane membrane experiment has shown that mycelial growth of C. acutatum was inhibited by 36% and 27% when treated with ATR697 and LON701, respectively. Culture filtrates (CFs) of two Trichoderma isolates inhibited the mycelial growth of C. acutatum in vitro. When red peppers were treated with spore suspensions of LON701 and ATR697, the disease severity (%) was 44.1% and 55.8%, respectively, in a curative method; while the disease severity (%) was 5% and 11.6%, in LON701- and ATR697-treated red peppers, respectively, in a preventive method. These results showed the suppression of disease severity (%) was relatively higher in the preventive method than in the curative method. Furthermore, Trichoderma isolates ATR697 and LON701 were resistant to commercial chemical fungicides in vitro, indicating these strains may also be used synergistically with a chemical fungicide (pyraclostrobin) against the growth of C. acutatum. There was no difference in the inhibition rate (%) of the pathogen between the treatment with LON701 alone and LON701+pyraclostrobin. Based on in vitro findings, ATR697 and LON701 played a role in effectively controlling red pepper anthracnose in field conditions, with LON701 treatment resulting in a disease rate of 14% when compared to ATR697, chemical, and non-treated controls. Overall, our study showed the ability of Trichoderma isolates to control red pepper anthracnose and their potential to develop as novel biocontrol agents to replace chemical fungicides for eco-friendly, sustainable agriculture.